Antibacterial nanofibrous hydrogel dressings, methods of making and using the same

CN118121749BActive Publication Date: 2026-10-20QINGDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410131357.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2026-10-20
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

[0005]现有抗菌纳米纤维水凝胶敷料的先进工艺仍存在一定局限性:首先,大部分纳米纤维水凝胶敷料是由纳米纤维与水凝胶复合组成的,复合过程复杂且不稳定;其次,负载银纳米颗粒抗菌的纳米纤维水凝胶敷料大多是通过前期分散或者后期吸附银纳米颗粒来实现的,容易造成银纳米颗粒分散不均匀或脱落

Benefits of technology

[0024]1、既具备纳米纤维的形态又具有水凝胶的特性。经过交联、耦合和原位合成的PAHy/AgNPs纳米纤维水凝胶仍保留了原纳米纤维的模拟ECM形态和结构的特点,所有样品都表现出快速的水溶胀特性,并在10分钟内达到溶胀平衡。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118121749B_ABST
    Figure CN118121749B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of biomedical materials, and particularly relates to an antibacterial nanofiber hydrogel dressing, a preparation method thereof and application of the antibacterial nanofiber hydrogel dressing in the field of wound healing. + The present application converts a nanofiber membrane into a nanofiber hydrogel through a cross-linking technology, and converts Ag in the nanofiber into AgNPs through an in-situ synthesis method, thereby constructing an antibacterial nanofiber hydrogel dressing with uniform dispersion of AgNPs, which has both nanofiber morphology and hydrogel performance. The nanofiber structure of the extracellular matrix (ECM) promotes cell adhesion, migration and proliferation. The hydrogel property makes it have a rapid water swelling. In addition, the antibacterial nanofiber hydrogel dressing has excellent antibacterial activity, good biocompatibility, and can promote the healing of skin wounds and collagen deposition at the wound site, and is an ideal new dressing for skin wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, and in particular to an antibacterial nanofiber hydrogel dressing, its preparation method, and the application of the antibacterial nanofiber hydrogel dressing in the field of wound healing. Background Technology

[0002] Wound healing is a relatively complex process, mainly involving four stages: hemostasis, inflammation, proliferation, and extracellular matrix (ECM) remodeling. The healing process can take several days or even months. Currently, dressings used for wound healing are mainly traditional cotton gauze and bandages, but they have some drawbacks, such as poor absorbency, easy adhesion to the wound leading to wound deterioration, and secondary injury.

[0003] Hydrogels possess the ability to retain large amounts of water, absorbing wound exudate and providing a moist environment. Studies have demonstrated that a moist environment can provide a beneficial microenvironment for accelerating wound healing. Therefore, numerous studies have begun exploring various hydrogel formulations as wound dressings. Furthermore, the performance of wound dressings largely depends on the morphology and structure of the scaffold. Electrospun nanofibers can largely mimic the inherent protein fibers of the ECM in terms of fiber scale, morphology, structure, and properties, and have been shown to significantly promote cell proliferation and differentiation, ECM deposition and remodeling, and new tissue regeneration, thus attracting widespread attention as a novel dressing material.

[0004] Antimicrobial properties are also crucial for wound dressing design. Prolonged exposure of skin wounds, especially chronic ones, is often accompanied by bacterial infection, further hindering wound healing. Among various antimicrobial agents, silver nanoparticles (AgNPs) have attracted significant attention and are used as effective broad-spectrum antimicrobial agents for constructing antimicrobial dressings. Nanoscale AgNPs exhibit a high specific surface area, enabling more effective resistance to microbial invasion. Therefore, AgNPs have been widely used in dressing materials to prevent wound infection. However, AgNPs are difficult to disperse uniformly in a polymer matrix, leading to uneven antimicrobial activity. Therefore, constructing an antimicrobial nanofiber hydrogel dressing with uniform AgNP dispersion, possessing both nanofiber morphology and hydrogel properties, is an effective strategy for preparing ideal wound dressings.

[0005] Current advanced processes for antibacterial nanofiber hydrogel dressings still have certain limitations: First, most nanofiber hydrogel dressings are composed of nanofibers and hydrogels, and the composite process is complex and unstable; second, nanofiber hydrogel dressings loaded with silver nanoparticles for antibacterial properties are mostly achieved through early dispersion or later adsorption of silver nanoparticles, which can easily lead to uneven dispersion or detachment of the silver nanoparticles. Therefore, developing a simple, stable, and uniform preparation process for producing antibacterial nanofiber hydrogel dressings that promote wound healing presents a certain challenge. Summary of the Invention

[0006] To address the aforementioned technical problems, and considering that the morphology, structure, and absorbency of wound dressings significantly influence cell adhesion, migration, and proliferation, this invention provides an antibacterial nanofiber hydrogel dressing and its preparation method. The antibacterial nanofiber hydrogel dressing is a novel dressing that possesses both nanofiber morphology and hydrogel properties, with uniformly dispersed silver nanoparticles, and is applied to skin tissue engineering dressings for wound healing.

[0007] This invention is achieved through the following technical solution:

[0008] An antibacterial nanofiber hydrogel dressing is obtained by cross-linking, coupling and in-situ synthesis of silver nanoparticles from a nanofiber membrane obtained by electrospinning. It has both nanofiber morphology and hydrogel properties, and the silver nanoparticles are uniformly dispersed.

[0009] The preparation method of the antibacterial nanofiber hydrogel dressing includes the following steps:

[0010] (1) Silver nitrate (AgNO3) and polysuccinimide (PSI) were mixed and electrospun to obtain PSI / AgNO3 nanofiber membrane;

[0011] (2) The nanofiber membrane was cross-linked by immersing it in ethylenediamine (ED) solution, and then hydrazine hydrate (HH) solution was added for coupling and in-situ synthesis. Polysuccinimide (PSI) and Ag were then used to synthesize the nanofiber membrane. + The nanofibers were converted into PAHy and AgNPs to obtain PAHy / AgNPs nanofiber hydrogel.

[0012] (3) The antibacterial nanofiber hydrogel is neutralized, depored and dried to obtain the antibacterial nanofiber hydrogel dressing.

[0013] Preferably, the mass ratio of silver nitrate to polysuccinimide is 0.5–1.5 wt.%.

[0014] Preferably, the specific steps of electrospinning are as follows:

[0015] a. After mixing silver nitrate and polysuccinimide, N,N-dimethylformamide (DMF) is added to obtain a mixed solution, wherein the mass fraction of polysuccinimide (PSI) in the mixed solution is 32% to 43 wt.%;

[0016] b. The mixed solution is loaded into a syringe and placed in a high-voltage DC electric field for electrospinning to obtain a nanofiber membrane. The electrospinning parameters are as follows: spinning voltage is +12 to 18 kV, spinning distance is 16 to 20 cm, feed rate is 0.6 to 1 mL / h, and receiving drum speed is 100 to 500 rpm.

[0017] Preferably, in step (2), the nanofiber membrane is first vacuum dried at 60°C for 24 hours to remove residual solvent, and then immersed in ethylenediamine (ED) solution. The nanofiber membrane needs to be processed to a suitable size before immersion. The concentration of ethylenediamine (ED) solution is 0.1-1 mol / L, the immersion time is 0.25-1 hour, and the concentration of hydrazine hydrate (HH) solution is 10-15%.

[0018] Preferably, in step (3), the antibacterial nanofiber hydrogel is neutralized with 5% acetic acid solution, then washed three times with deionized water, and placed in ethanol for depore removal; the depore-removed antibacterial nanofiber hydrogel dressing is dried in a vacuum oven for 24 hours.

[0019] The antibacterial nanofiber hydrogel dressing is applied in the field of wound healing. Specifically, it can be used to prepare chronic wound healing and repair materials, and as a skin tissue engineering dressing for wound healing.

[0020] The antibacterial nanofiber hydrogel dressing of this invention utilizes polymer materials with excellent biological properties. A high-voltage electric field is applied to the polymer solution, driving the spinning solution to be sprayed from the syringe needle in a mist or filamentous form onto a collecting roller, producing nanofibers with a diameter of several hundred nanometers. Electrospun nanofibers, with their small diameter and large specific surface area, have been shown to significantly promote cell attachment, growth, and proliferation, and can significantly promote in vivo wound healing compared to traditional dressings. However, dry electrospun nanofiber membranes cannot provide a moist environment conducive to wound healing. Furthermore, this invention utilizes cross-linking technology to successfully cross-link the nanofiber membrane into a nanofiber hydrogel, providing a moist microenvironment for wound healing. Research in this invention shows that PSI and AgNO3 do not undergo a chemical reaction during electrospinning, and the cross-linked nanofiber hydrogel retains the morphology of the nanofibers. It has been verified that in-situ synthesized silver nanoparticles are attached to the PAHy nanofibers of this nanofiber hydrogel dressing.

[0021] In addition, by optimizing the ratio of PSI and AgNO3, this invention has constructed a series of antibacterial nanofiber hydrogel dressings with different morphologies, mechanical properties and other physicochemical properties, as well as different antibacterial, cell proliferation and other biological properties.

[0022] Regarding antibacterial and bioactivity, this invention shows that, compared to PAHy / AgNPs-0 without AgNPs, PAHy / AgNPs-0.5 loaded with AgNPs exhibits significantly enhanced antibacterial activity, and both demonstrate good cell compatibility. Furthermore, compared to traditional cotton dressings, PAHy / AgNPs nanofiber hydrogel dressings effectively promote wound healing and collagen deposition.

[0023] Compared with traditional dressings, the PAHy / AgNPs nanofiber hydrogel dressing provided by this invention has the following beneficial effects on the treatment of skin wounds:

[0024] 1. It possesses both the morphology of nanofibers and the properties of hydrogels. The PAHy / AgNPs nanofiber hydrogels synthesized through cross-linking, coupling, and in-situ synthesis still retain the characteristics of the original nanofibers' simulated ECM morphology and structure. All samples exhibited rapid water swelling characteristics and reached swelling equilibrium within 10 minutes.

[0025] 2. Excellent antibacterial activity. PAHy / AgNPs nanofiber hydrogels showed inhibition rates of over 99.99% against both Escherichia coli and Staphylococcus aureus. PAHy / AgNPs-0.5 exhibited clear inhibition zones, with an inhibition zone diameter of 5.8±0.3 mm against Staphylococcus aureus and a non-completely transparent inhibition zone with a diameter of 10.0±0.7 mm against Escherichia coli.

[0026] 3. It has good biocompatibility. After 3 days of culture, the survival rate of HDFs of PAHy / AgNPs-0 was 100.9±6.1%, that of PAHy / AgNPs-0.5 was 97.3±3.3%, and that of PAHy / AgNPs-1.0 was 96.5±1.1%.

[0027] 4. Promotes wound healing in mouse skin wounds. Animal experiments have shown that adding appropriate amounts of AgNPs to PAHy nanofibers can significantly accelerate wound healing. After 14 days of treatment, the wound contraction rate of PAHy / AgNPs-0.5 (66.9±2.8%) was significantly greater than that of the control group (26.93±2.0%). Histological staining showed that wounds treated with PAHy / AgNPs nanofiber hydrogel dressings had significantly more mature collagen deposition. Attached Figure Description

[0028] Figure 1This is a schematic diagram of the preparation process of the antibacterial nanofiber hydrogel dressing described in this invention;

[0029] Figure 2 The surface morphology of the PSI / AgNO3 nanofiber membrane and PAHy / AgNPs nanofiber hydrogel described in Example 1 is shown in Figure 1. A represents the SEM characterization of the PSI / AgNO3 nanofiber membrane and PAHy / AgNPs nanofiber hydrogel, B is a photograph of the actual product, and C represents the average fiber diameter.

[0030] Figure 3 The image shows the surface morphology of AgNPs in the PAHy / AgNPs nanofiber hydrogel of Example 1; where A is a TEM image of the nanofibers loaded with AgNPs, B is the HAADF image and corresponding EDS image of the nanofibers in PAHy / AgNPs-1.5, and C is the average diameter of the AgNPs.

[0031] Figure 4 The physicochemical properties of the PAHy / AgNPs nanofiber hydrogel in Example 1 are shown below; where A represents the FTIR spectra of PAHy / AgNPs-0 and PAHy / AgNPs-1.0 after crosslinking and HH reaction, and B represents the dynamic swelling ratio.

[0032] Figure 5 The physicochemical properties of the PAHy / AgNPs nanofiber hydrogel in Example 1 are shown below; where A represents Young's modulus, tensile strength, and elongation at break under dry conditions, and B represents Young's modulus, tensile strength, and elongation at break under wet conditions.

[0033] Figure 6 The antibacterial activity of PAHy / AgNPs nanofiber hydrogel in Example 1 against Escherichia coli and Staphylococcus aureus;

[0034] Figure 7 Biocompatibility analysis of PAHy / AgNPs nanofiber hydrogel in Example 1; wherein, A is the quantitative measurement of HDFs cell viability after three days of culture, and B is the immunofluorescence staining image of HDFs cultured on PAHy / AgNPs-0 and PAHy / AgNPs-1.5 on the third day.

[0035] Figure 8 The results of the study on the promotion of in vivo wound healing by the PAHy / AgNPs nanofiber hydrogel dressing described in Example 1 are shown. Among them, A is the wound site photographs of the control group and three different PAHy / AgNPs groups on postoperative days 0, 3, 5, 7, 10 and 14, and B is the quantitative analysis of wound contraction rate at predetermined time intervals in four different groups.

[0036] Figure 9 The histological evaluation results are as described in Example 1. Detailed Implementation

[0037] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0038] like Figure 1 As shown, the present invention provides an antibacterial nanofiber hydrogel dressing, which is obtained by crosslinking, coupling and in-situ synthesis of silver nanoparticles from a nanofiber membrane obtained by electrospinning process; the antibacterial nanofiber hydrogel is a novel dressing that has both nanofiber morphology and hydrogel properties, and the silver nanoparticles are uniformly dispersed.

[0039] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.

[0040] Example 1

[0041] I. Preparation of Antibacterial Nanofiber Hydrogel Dressing

[0042] 1. Preparation of PSI / AgNO3 nanofiber membranes

[0043] Silver nitrate (AgNO3) and polysuccinimide (PSI) were added to N,N-dimethylformamide (DMF) solution at mass ratios of 0, 0.5 wt%, 1.0 wt%, and 1.5 wt%, respectively, to obtain four mixed solutions, with a PSI mass fraction of 34% in each solution. The mixed solutions were loaded into a syringe and electrospun in a high-voltage DC electric field. The electrospinning parameters were as follows: spinning voltage +15 kV, spinning distance 18 cm, feed rate 0.7 mL / h, and receiving drum speed 300 rpm, to obtain PSI / AgNO3 nanofiber membranes. The membranes were then vacuum dried at 60 °C for 24 h to remove residual solvent.

[0044] 2. Preparation of PAHy / AgNPs nanofiber hydrogels

[0045] The dried PSI / AgNO3 nanofiber membrane was immersed in 0.25 mol / L ethylenediamine (ED) solution for 0.5 h for crosslinking. 12.5% ​​hydrazine hydrate (HH) solution was added to the immersion solution for coupling and in-situ synthesis to convert PSI and Ag+ into PAHy and AgNPs. The resulting antibacterial nanofiber hydrogel was neutralized with 5% acetic acid solution, then washed three times with deionized water and deporated in ethanol. The deporated antibacterial nanofiber hydrogel dressing was dried in a vacuum oven for 24 h. The resulting PAHy / AgNPs nanofiber hydrogels were designated PAHy / AgNPs-0, PAHy / AgNPs-0.5, PAHy / AgNPs-1.0, and PAHy / AgNPs-1.5, respectively, and their performance was tested and evaluated.

[0046] II. Characterization of the wound healing effect of antibacterial nanofiber hydrogel dressing

[0047] 1. Preparation and characterization of PAHy / AgNPs nanofiber hydrogels

[0048] This embodiment first successfully prepared a PSI / AgNO3 nanofiber membrane using electrospinning. Figure 2 B), subsequently transformed into PAHy / AgNPs nanofiber hydrogel through ED crosslinking reaction, HH coupling, and in-situ synthesis reaction. Figure 2 B). SEM image ( Figure 2 A) shows that a smooth, uniform, and bead-free PSI / AgNO3 nanofiber membrane was successfully prepared, indicating that the PSI / AgNO3 solution has good electrospinning properties. Furthermore, the morphology of the PAHy / AgNPs nanofiber hydrogel remained largely unchanged except for slight fusion, indicating that the original nanofiber morphology can be maintained. This suggests that ED crosslinking and HH reaction did not significantly affect the fiber morphology in the prepared hydrogel matrix. The average fiber diameter of the nanofibers prepared from pure PSI (…) Figure 2 C) has a wavelength of 628.5±108.1 nm, significantly larger than that of PSI / AgNO3 nanofibers bound to AgNO3 (PSI / AgNO3-0.5: 516.8±129.1 nm, PSI / AgNO3-1.0: 534.2±84.9 nm, PSI / AgNO3-1.5: 474.1±78.5 nm). This is because AgNO3 in solution is in the form of Ag... + and NO3 - The form of AgNO3 solution increases its conductivity, leading to a larger electric field force on the AgNO3 solution jet during electrospinning, stretching it into nanofibers with smaller diameters. The average fiber diameter of the samples treated with ED and HH increased. Figure 2C). Specifically, the average fiber diameters of PAHy / AgNPs-0, PAHy / AgNPs-0.5, PAHy / AgNPs-1.0, and PAHy / AgNPs-1.5 were 773.0±119.5 nm, 650.9±81.2 nm, 651.7±82.8 nm, and 640.9±85.1 nm, respectively. The size, shape, and distribution of AgNPs in PAHy nanofibers were observed and studied using transmission electron microscopy. Figure 3 A). Due to the large diameter of PAHy / AgNPs nanofibers, electron beams have difficulty penetrating the sample. Therefore, the HAADF mode was used, and it was found that most AgNPs exhibit a spherical morphology with a size of 10-50 nm. Compared with PAHy / AgNPs-1.0 and PAHy / AgNPs-1.5, the number of AgNPs distributed in PAHy / AgNPs-0.5 nanofibers is relatively low. Figure 3 B shows the HAADF image of PAHy / AgNPs-1.5, revealing an overlapping distribution of AgNPs throughout the nanofibers. The AgNPs in PAHy / AgNPs-1.5 (36.2 ± 11.4 nm) exhibit significantly larger diameters than those in PAHy / AgNPs-0.5 (20.5 ± 3.8 nm) and PAHy / AgNPs-1.0 (28.0 ± 9.5 nm), indicating that the addition of more AgNO3 leads to the formation of more and larger AgNPs. Figure 3 C).

[0049] This embodiment utilizes FTIR spectroscopy to determine the chemical groups of different PSI / AgNO3 nanofiber membranes, ED-crosslinked PSI / AgNO3 nanofiber membranes, and PAHy / AgNPs nanofiber hydrogels. Figure 4 A). For PSI / AgNO3-0, 1704cm -1 and 1795cm -1 The adjacent band at that location is attributed to two adjacent carbonyl groups (C(=O)N) in the succinimide ring of the PSI chain. C=O (Symmetric stretching). PSI / AgNO3-1.0 and PSI / AgNO3-0 showed almost identical curves, indicating that no chemical reaction occurred between PSI and AgNO3 after the addition of AgNO3. After the crosslinking reaction of PSI / AgNO3-0 and PSI / AgNO3-1.0 nanofiber membranes, the crosslinking thickness was 1795 cm⁻¹. -1 1704cm -1 and 1360cm -1 The disappearance of the peak indicates the opening of the succinimide ring. (3254 cm⁻¹) -1 (stretching σ in -NH(CO)-)N-H ), 1531cm -1 The new peak (-NH(CO)-amide II δ) N-H (bent) and 1639cm -1 The dense peak at (σ of stretchable amide I) C=O This confirmed that the cross-linking reaction occurred between PSI and ED. Due to the complexation reaction between silver ions and amino groups, at 1479 cm⁻¹... -1 A slight difference was found. After the HH reaction, 3254 cm was observed. -1 1639cm -1 and 1531cm -1 The peaks at the point are dense, indicating that the succinimide ring remaining in the PSI is opened, generating PHAy.

[0050] The dynamic water swelling behavior of the sample in this embodiment is as follows: Figure 4 As shown in B, all samples exhibited rapid water swelling characteristics and reached swelling equilibrium within 10 minutes. The final swelling ratios of PAHy / AgNPs-0, PAHy / AgNPs-0.5, PAHy / AgNPs-1.0, and PAHy / AgNPs-1.5 were 13.7±2.4 g / g, 11.7±2.3 g / g, 10.5±0.5 g / g, and 7.5±1.1 g / g, respectively. Due to the large specific surface area and abundant pores of PAHy nanofibers, water can rapidly penetrate into the interior of the hydrogel, and all nanofiber membranes exhibited a rapid response upon exposure to water. Furthermore, due to the interaction between AgNPs and PAHy, the swelling ratio of PAHy / AgNPs nanofiber hydrogels was shown to decrease with increasing AgNP count.

[0051] Tensile test results show that, under dry conditions, PAHy / AgNPs-0, PAHy / AgNPs-0.5, and PAHy / AgNPs-1.0 exhibit similar Young's modulus and fracture strength. Figure 5A) The Young's moduli of PAHy / AgNPs-0, PAHy / AgNPs-0.5, and PAHy / AgNPs-1.0 are 199.8±53.3MPa, 145.1±17.5MPa, and 173.3±31.3MPa, respectively; the ultimate tensile strengths are 6.1±0.7MPa, 5.7±0.8MPa, and 6.3±1.6MPa, respectively. In contrast, PAHy / AgNPs-1.5 exhibits enhanced Young's modulus (304.7±37.3MPa) and fracture strength (8.4±1.8MPa). Furthermore, all four samples exhibited similar elongation at break (PAHy / AgNPs: 25.9±7.8%, PAHy / AgNPs-0.5: 26.6±5.6%, PAHy / AgNPs-1.0: 21.6±3.1%, PAHy / AgNPs-1.5: 20.2±7.5%), with no significant differences found. Under humid conditions ( Figure 5 (B) All samples exhibited significantly reduced Young's modulus and fracture strength. The samples showed similar fracture strengths under humid conditions (PAHy / AgNPs-0: 0.12 ± 0.02 MPa, PAHy / AgNPs-0.5: 0.14 ± 0.02 MPa, PAHy / AgNPs-1.0: 0.12 ± 0.03 MPa, PAHy / AgNPs-1.5: 0.11 ± 0.01 MPa). Compared with AgNPs-bonded PAHy / AgNPs nanofiber hydrogels, pure PAHy nanofiber hydrogels exhibited lower Young's modulus (0.15±0.02 MPa for PAHy / AgNPs-0, 0.20±0.03 MPa for PAHy / AgNPs-0.5, 0.31±0.04 MPa for PAHy / AgNPs-1.0, and 0.30±0.05 MPa for PAHy / AgNPs-1.5) and greater elongation at break (155.8±16.6% for PAHy / AgNPs-0, 66.0±4.8% for PAHy / AgNPs-0.5, 8.1±7.4% for PAHy / AgNPs-1.0, and 44.4±6.9% for PAHy / AgNPs-1.5). The better tensile properties of PAHy / AgNPs-1.5 under dry conditions are likely attributed to the higher fiber packing density during the drying process. Under wet conditions, water penetrates the membrane and cross-linked polymer network within the matrix, weakening the matrix strength.

[0052] 2. PAHy / AgNPs nanofiber hydrogels can significantly enhance antibacterial activity.

[0053] Bacterial infections pose a significant threat to skin wounds, and the ability of wound dressings to prevent infection by inhibiting bacterial growth is crucial. This embodiment evaluates the antibacterial properties of four different nanofiber hydrogels using the plating and diffusion methods. Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus were used as representative species. Figure 6 As shown, the antibacterial results of the plating method indicate that all four types of PAHy nanofiber hydrogels, both containing and without AgNPs, exhibit significant antibacterial activity against Escherichia coli and Staphylococcus aureus, with inhibition rates exceeding 99.99%. The excellent antibacterial properties of the PAHy / AgNPs-0 nanofiber hydrogel may be attributed to its abundant positively charged amino groups, which can interact with negatively charged components in the bacterial membrane, leading to changes in barrier properties and even bacterial death.

[0054] The results of the diffusion method are as follows Figure 6 As shown, no inhibition zone was observed in PAHy / AgNPs-0. In contrast, PAHy / AgNPs-0.5 exhibited a clear inhibition zone, with a diameter of 5.8 ± 0.3 mm against Staphylococcus aureus. A non-completely transparent inhibition zone with a diameter of 10.0 ± 0.7 mm was observed against Escherichia coli. Furthermore, PAHy / AgNPs-1.0 and PAHy / AgNPs-1.5 failed to show obvious inhibition zones. The superior contact antibacterial properties of PAHy / AgNPs-0.5 may be due to the smaller size of the AgNPs in the PAHy / AgNPs-0.5 nanofibers. Previous studies have demonstrated that smaller AgNPs can exhibit faster oxidation and Ag... + Release rate. Therefore, PAHy / AgNPs-0.5 nanofiber hydrogel exhibits better antibacterial activity.

[0055] 3. Biocompatibility testing of PAHy / AgNPs nanofiber hydrogel

[0056] In this embodiment, HDFs were used as the necessary cell model, seeded and cultured on four different PAHy / AgNPs nanofiber hydrogels, and their in vitro biocompatibility was further evaluated. Figure 7A showed that after 3 days of culture, the survival rate of HDFs from PAHy / AgNPs-0 was 100.9±6.1%, PAHy / AgNPs-0.5 was 97.3±3.3%, and PAHy / AgNPs-1.0 was 96.5±1.1%. There was no significant difference among these three samples, indicating good biocompatibility. In contrast, the cell survival rate of PAHy / AgNPs-1.5 was significantly reduced (81.4±9.4%), suggesting that the PAHy / AgNPs-1.5 nanofiber hydrogel exhibited some degree of cytotoxicity due to the excessive number and large particle diameter of AgNPs. Immunofluorescence staining was further used to visualize the cytoskeleton and nuclei of HDFs after 3 days of culture. Figure 7 B). We found that HDFs exhibited both spindle-shaped and elongated morphologies on both PAHy / AgNPs-0 and PAHy / AgNPs-1.5, but the cell count on PAHy / AgNPs-1.5 was significantly lower than that on PAHy / AgNPs-0. Due to the low biocompatibility of PAHy / AgNPs-1.5 nanofiber hydrogel, the following animal studies were conducted using only three other different PAHy / AgNPs nanofiber hydrogels.

[0057] 4. Animal experiments and histological analysis of PAHy / AgNPs nanofiber hydrogels

[0058] This study investigated the in vivo wound healing properties of three PAHy / AgNPs nanofiber hydrogel dressings using a mouse full-thickness skin wound model. Commercial cotton gauze was used as a control group. Real photographs of dynamic wound closure in different sample groups are shown below. Figure 8 As shown in the figure. Compared with the control group, all three different PAHy / AgNPs nanofiber hydrogel dressings showed significantly faster wound closure. After 7 days, the wound contraction rate of PAHy / AgNPs-0.5 (47.6±1.5%) was significantly greater than that of the other three groups (control group: 16.5±1.5%, PAHy / AgNPs-0: 18.7±0.5%, PAHy / AgNPs-1.0: 26.9±1.1%). After 14 days of treatment, the wound contraction rates of PAHy / AgNPs-0 (67.4±1.3%) and PAHy / AgNPs-0.5 (66.9±2.8%) were significantly greater than those of the control group (26.93±2.0%) and PAHy / AgNPs-1.0 (40.7±1.7%). These results indicate that, compared with traditional cotton yarn, PAHy / AgNPs nanofiber hydrogel dressings have the ability to promote wound healing, and that adding AgNPs appropriately to PAHy nanofibers can significantly accelerate the wound healing process.

[0059] The newly formed skin tissue in each group was further characterized by H&E staining and Masson staining to explore the histological structure of the regenerated skin tissue at the wound site 14 days later. Figure 9 Clearly, the control group showed no significant re-epithelialization at the wound site, instead exhibiting large areas of scleroderma. In contrast, the other three different PAHy / AgNPs nanofiber hydrogels all demonstrated a significant neoepithelial layer at the wound site. Furthermore, wound sites treated with PAHy / AgNPs-0 and PAHy / AgNPs-0.5 showed significantly more and more mature collagen deposition compared to the control group and PAHy / AgNPs-1.0 at day 14, indicating a significant improvement in wound healing quality.

[0060] Example 2

[0061] The preparation method of the antibacterial nanofiber hydrogel dressing of the present invention includes the following steps:

[0062] 1. Preparation of PSI / AgNO3 nanofiber membranes

[0063] AgNO3 and PSI were added to a DMF solution at a mass ratio of 1.0 wt%, with the PSI mass fraction in the mixed solution being 32%. The mixed solution was loaded into a syringe and placed in a high-voltage DC electric field for electrospinning. The electrospinning parameters were as follows: spinning voltage +12 kV, spinning distance 16 cm, feed rate 0.6 mL / h, and receiving drum speed 100 rpm. A PSI / AgNO3 nanofiber membrane was obtained and vacuum dried at 60 °C for 24 h to remove residual solvent.

[0064] 2. Preparation of PAHy / AgNPs nanofiber hydrogels

[0065] The dried PSI / AgNO3 nanofiber membrane was immersed in 0.1 mol / L ethylenediamine (ED) solution for 0.25 h for crosslinking. Coupling was then performed by adding 10% hydrazine hydrate (HH) solution to the immersion solution, and PSI and AgNO3 nanofibers were synthesized in situ. + The antibacterial nanofiber hydrogel was converted into PAHy and AgNPs. The resulting antibacterial nanofiber hydrogel was neutralized with 5% acetic acid solution, then washed three times with deionized water, and placed in ethanol for depore removal. The depore-removed antibacterial nanofiber hydrogel dressing was dried in a vacuum oven for 24 hours to obtain the final product.

[0066] Example 3

[0067] The preparation method of the antibacterial nanofiber hydrogel dressing of the present invention includes the following steps:

[0068] 1. Preparation of PSI / AgNO3 nanofiber membranes

[0069] AgNO3 and PSI were added to a DMF solution at a mass ratio of 1.0 wt%, with the PSI mass fraction in the mixed solution being 43%. The mixed solution was loaded into a syringe and placed in a high-voltage DC electric field for electrospinning. The electrospinning parameters were as follows: spinning voltage +18 kV, spinning distance 20 cm, feed rate 1 mL / h, and receiving drum speed 500 rpm. A PSI / AgNO3 nanofiber membrane was obtained and vacuum dried at 60 °C for 24 h to remove residual solvent.

[0070] 2. Preparation of PAHy / AgNPs nanofiber hydrogels

[0071] The dried PSI / AgNO3 nanofiber membrane was immersed in 1 mol / L ethylenediamine (ED) solution for 1 h for crosslinking. 15% hydrazine hydrate (HH) solution was added to the immersion solution for coupling, and PSI and AgNO3 were synthesized in situ. + The antibacterial nanofiber hydrogel was converted into PAHy and AgNPs. The resulting antibacterial nanofiber hydrogel was neutralized with 5% acetic acid solution, then washed three times with deionized water, and placed in ethanol for depore removal. The depore-removed antibacterial nanofiber hydrogel dressing was dried in a vacuum oven for 24 hours to obtain the final product.

Claims

1. An antibacterial nanofiber hydrogel dressing, characterized in that: It is a novel dressing that is obtained by cross-linking, coupling and in-situ synthesis of silver nanoparticles from nanofiber membranes obtained by electrospinning. It has both nanofiber morphology and hydrogel properties, and the silver nanoparticles are uniformly dispersed. The preparation method of the antibacterial nanofiber hydrogel dressing includes the following steps: (1) Nanofiber membranes were obtained by electrospinning a mixture of silver nitrate (AgNO3) and polysuccinimide (PSI), with a mass ratio of silver nitrate to polysuccinimide of 0.5~1.5 wt.%. (2) The nanofiber membrane was cross-linked by immersing it in ethylenediamine (ED) solution, and then hydrazine hydrate (HH) solution was added for coupling and in-situ synthesis. Polysuccinimide (PSI) and Ag were then used to cross-link the nanofiber membrane. + They were converted into PAHy and AgNPs to obtain nanofiber hydrogels; (3) The antibacterial nanofiber hydrogel is neutralized, depored and dried to obtain the antibacterial nanofiber hydrogel dressing.

2. The antibacterial nanofiber hydrogel dressing according to claim 1, characterized in that: The specific steps of electrospinning are as follows: a. Silver nitrate and polysuccinimide are mixed, and then N,N-dimethylformamide (DMF) is added to obtain a mixed solution, wherein the mass fraction of polysuccinimide (PSI) in the mixed solution is 32%~43 wt.%. b. The mixed solution is loaded into a syringe and placed in a high-voltage DC electric field for electrospinning to obtain a nanofiber membrane.

3. The antibacterial nanofiber hydrogel dressing according to claim 2, characterized in that: The electrospinning parameters are as follows: spinning voltage is +12~18 kV, spinning distance is 16~20 cm, feed rate is 0.6~1 mL / h, and receiving drum speed is 100~500 rpm.

4. The antibacterial nanofiber hydrogel dressing according to claim 1, characterized in that: In step (2), the nanofiber membrane is first vacuum dried to remove the residual solvent, and then immersed in ethylenediamine (ED) solution.

5. The antibacterial nanofiber hydrogel dressing according to claim 1, characterized in that: In step (2), the concentration of ethylenediamine (ED) solution is 0.1~1 mol / L, and the soaking time is 0.25~1 h.

6. The antibacterial nanofiber hydrogel dressing according to claim 1, characterized in that: In step (2), the concentration of hydrazine hydrate (HH) solution is 10~15%.

7. The antibacterial nanofiber hydrogel dressing according to claim 1, characterized in that: In step (3), the neutralization reaction is carried out using acetic acid solution, the depore removal is carried out using ethanol, and the drying is carried out in a vacuum oven.

Citation Information

Patent Citations

  • Method for preparing polyaspartic acid type hydrogel

    CN102643441A

  • Composite nanofiber and preparation method thereof

    CN107964696A